2021
DOI: 10.3390/jcm10040760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylprednisolone on Ventilator-Free Days in Mechanically Ventilated Patients with Acute Respiratory Distress Syndrome and COVID-19: A Retrospective Study

Abstract: Objectives: There are limited data regarding the efficacy of methylprednisolone in patients with acute respiratory distress syndrome (ARDS) due to coronavirus disease 2019 (COVID-19) requiring invasive mechanical ventilation. We aimed to determine whether methylprednisolone is associated with increases in the number of ventilator-free days (VFDs) among these patients. Design: Retrospective single-center study. Setting: Intensive care unit. Patients: All patients with ARDS due to confirmed SARS-CoV-2 infection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Biological drugs are a risk factor for serious infection in rheumatoid arthritis [14]. Although the COVID-19 trials showed no difference in the incidence of infections in either TCZ or BRT groups, compared to that in the placebo [4,8], one retrospective study showed that concomitant use of TCZ and methylprednisolone is a risk factor for bacteremia [15]. Besides, whether there is a difference in the risk of developing infections between TCZ and BRT has not been evaluated earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Biological drugs are a risk factor for serious infection in rheumatoid arthritis [14]. Although the COVID-19 trials showed no difference in the incidence of infections in either TCZ or BRT groups, compared to that in the placebo [4,8], one retrospective study showed that concomitant use of TCZ and methylprednisolone is a risk factor for bacteremia [15]. Besides, whether there is a difference in the risk of developing infections between TCZ and BRT has not been evaluated earlier.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing, 47 articles were removed for the following reasons: intervention group involved other agents (n = 16), non-comparative studies (n = 13), data cannot be extracted (n = 11), comparison between different glucocorticoids (n = 4), and duplicate data (n = 3). Finally, 5 RCTs [14] , [16] , [26] , [36] , [37] and 28 non-RCTs [13] , [15] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] met the criteria for inclusion in the meta-analysis. A flow diagram that describes the search process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis, there were 29 studies [13] , [14] , [15] , [16] , [17] , [19] , [20] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [42] , [43] , [45] providing the information regarding short-term mortality. After pooling data, short-term mortality was seen in 468 (21.8 %) of 2146 patients receiving methylprednisolone and 496 (24.8 %) of 1996 receiving no glucocorticoids treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, mean ventilator days and ventilator-free days in COVID-19 patients were 10.54 and 3.92days, respectively which was similar to the published literature. 18 When compared to their non-COVID-19 counterpart, these durations were much longer, reflecting a much larger resource utilization of COVID-19 patients. This trend also reflects not only increased duration of ventilation in the COVID-19 group but also prolonged post-ventilation ICU stay in this group.…”
Section: Discussionmentioning
confidence: 99%